Explain the theoretical foundations of digital modernism and its educational implications - Fallah, Amir Hosein Soltani; Farahani, Mohsen Farmahini (International Journal of Psychosocial Rehabilitation, 2020)
Today, digital is one of the most common and familiar words that we are all involved with in some way and has left various effects on aspects of individual and social life, including education. This project aims to explain the theoretical foundations of digital modernism as a new paradigm that was born after postmodernism and also to express its educational implications. The method of the present research is done by descriptive method and concept analysis, which first by explaining the concepts of digital modernism and then by analyzing its concepts to obtain the educational implications of digital modernism. Since in the present study, the type of data is non-statistical, so the method of data collection is library. The research findings show that despite the fact that DJ Modernism is historically behind postmodern, but from a cognitive point of view, it is a concept that oscillates between modernity and postmodern. Also, the educational implications of digital modernism can be examined in at least six areas, all of which have a common chapter based on digital.